The response of survivin to hypoxia and the functional roles of its subcellular pools. - Fezovich, Alexander (2023)
Survivin is a highly conserved and multifaceted protein with well characterised roles in mitosis and inhibition of apoptosis. Largely absent from normal adult tissue, survivin is highly expressed in most cancers and is an attractive target for cancer therapeutics. Further evidence has implicated survivin in a number of additional pathways, including cell metabolism, DNA repair and autophagy. These functions are associated with distinct subcellular pools of survivin, located in the cytoplasm, nucleus and mitochondria.